Organising From the Road: Private Hire Drivers, Platforms, and Independent Unions - Kearsey, Joe (2024)
The aim of this thesis is to understand what factors have informed private hire drivers’ class-based mobilisations, and how these workers' relation to capital, the labour process, and their position within society more generally has influenced their current form of collective organisation. This has been undertaken through a participatory and partisan inquiry, embedded within processes of collective organisation alongside organisers and drivers in the United Private Hire Drivers branch of the Independent Workers' Union of Great Britain (UPHD-IWGB). The thesis is an ethnographic case study which draws on forms of co-produced knowledge from within the collective organisation process and forms an account and analysis of a six-month attachment with the union branch.